1995
DOI: 10.1037/0012-1649.31.5.866
|View full text |Cite
|
Sign up to set email alerts
|

Relations between children's overestimation of their physical abilities and accident proneness.

Abstract: Two experiments examined developmental changes in the accuracy of children's judgments about their physical abilities. Experiment 1 showed that 6-and 8-year-olds overestimated their ability to perform tasks just beyond and well beyond their ability. Adults only had difficulty making judgments about tasks just beyond their ability. Experiment 2 investigated how experience with performing activities influences judgments about physical abilities. Six-year-olds again overestimated their ability to perform tasks ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
164
3
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(195 citation statements)
references
References 36 publications
17
164
3
11
Order By: Relevance
“…It seemed as if children misjudge the affordance of the gap to cross and their locomotion took longer to clear the roadway. This discrepancy of judgment and motorability between children and adults is consistent with the previous research on child cyclists' perception of affordance (Plumert et al, 2004) and is compatible with the concept that children make errors in perceiving affordances which might be a cause of childhood injuries (Plumert, 1995).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It seemed as if children misjudge the affordance of the gap to cross and their locomotion took longer to clear the roadway. This discrepancy of judgment and motorability between children and adults is consistent with the previous research on child cyclists' perception of affordance (Plumert et al, 2004) and is compatible with the concept that children make errors in perceiving affordances which might be a cause of childhood injuries (Plumert, 1995).…”
Section: Discussionsupporting
confidence: 80%
“…Plumert andco-investigators (2004, 2007) examined how child and adult cyclist chose gaps when they crossed traffic-filled intersections in virtual environment. Both the studies showed that children were less skillful in initiating movement and took longer to cross the road.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61] Because a large proportion of injury mechanisms resulting in forearm fracture are minor, these specific injuries may be less amenable to primary injury prevention strategies focusing on mechanism. 62 The unique public health aspects of forearm fracture injuries merit broadening the concept of injury prevention to include bone health promotion in at-risk pediatric populations.…”
Section: Discussionmentioning
confidence: 99%
“…Las campañas para concienciar de que no se debe beber si se desea nadar, o que se debe ser cuidadoso cuando se está medicando, son muy habituales. No obstante, hay un aspecto que se ha analizado poco tanto en niños como en mayores Plumert, 1995Plumert, , 2003 y es el referido a la inadecuada valoración que hacen de sus propios recursos en relación a las demandas de la situación, lo que en muchas ocasiones tiene como consecuencia comportamientos osados y atrevidos que pueden llevar a situaciones difíciles e incluso fatales.…”
Section: Más Allá De La Infanciaunclassified